Outcome of surgical treatment of 54 Periprosthetic femoral fractures after total hip arthroplasty at mid term follow-up - Akkawi, Ibrahim; Fabbri, Daniele; Romantini, Matteo; Laus, Massimo; Calogero, Alfonso (Acta Biomedica Atenei Parmensis, 2021)
Purpose: The aim of the present study was to review the outcome of the surgical treatment of 54 periprosthetic femoral fractures (PFF) after total hip arthroplasty at a mean follow-up of 45 months. At final follow-up, the clinical outcome was measured using the Harris Hip score (HHS), the Karnofsky score (KS), while, the radiographic results were evaluated using the Beals and Tower’s criteria.Results: There were 13 post-operative complications that occurred in 10 patients with an overall re-operation rate of 11%. At final follow-up the mean HHS was 64 (range 20-100) and the mean KS was 66 (range 30-100). The radiological results were excellent in 89%, good in 9% and poor 2% of patients. The mortality rate was 0% at 3 months and 3.7% at one year post-operatively.The mean last HHS and KS of patients older than 75 years or with comorbidities were lower than that of patients younger than 75 years or without comorbidities.Conclusions: Although this study have shown that the surgical treatment of PFF was associated with a low re-operative rate, a good to excellent radiological results and a low mortality rate at 3 months and 1 year postoperatively, there was a marked functional deterioration in many patients. This decline of function could be attributed to the advanced age of patients and the presence of comorbidities.